The influence of hydrogen sulfide contaminations on hydrogen production in chemical looping processes. (1st January 2022) - Stoppacher, B.; Bock, S.; Malli, K.; Lammer, M.; Hacker, V.
Highlights: First investigation of the impact of H2 S on chemical looping hydrogen production. Strong temperature dependency of hydrogen sulfide chemisorption. ICP-EOS analysis confirmed the chemisorption of sulfur on oxygen carrier material. Significant sulfur contamination of product hydrogen in the oxidation phase. Fulfillment of the overall sulfur mass balance within a mean deviation of 3.7%. Abstract: Chemical looping with iron-based oxygen carriers enables the production of hydrogen from various fossil and biogenic primary energy sources. In applications with real producer gases, such as biogas or gasified biomass, hydrogen sulfide represents one of the most challenging contaminants. The impact of H2 S on the reactivity of a Fe2 O3 /Al2 O3 oxygen carrier material in chemical looping hydrogen production was investigated in the present work. First, potential sulfur deactivation mechanisms are discussed in detail on the basis of thermodynamic data. Afterwards, an experimental study in a fixed-bed reactor system gave experimental evidence on the fate of sulfur in chemical looping hydrogen systems. The chemisorption of hydrogen sulfide (H2 S) was identified as the main cause for the accumulative adsorption of H2 S in the reduction phase and was confirmed by ex-situ ICP-EOS analysis. In the subsequent steam oxidation step, significant quantities of H2 S were released resulting in an undesirable contamination of the hydrogen product gas. The reason was found as weakened sulfur bonds through increasing reactor temperatures caused by the exothermic oxidation reactions. In additional air oxidation steps no further contaminants as sulfur dioxide were identified. A profound interpretation was achieved through the fulfillment of the overall sulfur mass balance within a mean deviation of 3.7%. Quantitative investigations showed that the hydrogen consumption decreased by 12% throughout the reduction phase in the event of 100 ppm H2 S in the feed gas.